An introduction to metaphilosophy - Overgaard, S{u296E}; Gilbert, Paul, 1942-; Burwood, Stephen, 1959- (Cambridge : Cambridge University Press, 2013)
'What is philosophy? How should we do it? Why should we bother to? These are the kinds of questions addressed by metaphilosophy - the philosophical study of the nature of philosophy itself. Students of philosophy today are faced with a confusing and daunting array of philosophical methods, approaches and styles and also deep divisions such as the notorious rift between analytic and Continental philosophy. This book takes readers through a full range of approaches - analytic versus Continental, scientistic versus humanistic,'pure' versus applied - enabling them to locate and understand these different ways of doing philosophy. Clearly and accessibly written, it will stimulate reflection on philosophical practice and will be invaluable for students of philosophy and other philosophically inclined readers'--
1. Introduction: what good is metaphilosophy? -- 2. What is philosophy? -- 3. Philosophy, science and the humanities -- 4. The data of philosophical arguments -- 5. Analytic and continental philosophy -- 6. Philosophy and the pursuit of truth -- 7. What is good philosophy? -- 8. What good is philosophy?.
Includes index and bibliographical references (pages 219-232).
Keywords: Philosophy